Mechanism of traditional Chinese medicine with GLUT1 as a potential therapeutic target for diabetic nephropathy - Fu Shao-jie; Zhang Li; Wang Xue-yao; Xu Zhong-gao (Linchuang shenzangbing zazhi)
ObjectiveTo explore the active ingredients of traditional Chinese medicine （TCM） with GLUT1 as a potential target and elucidate its possible therapeutic mechanism for diabetic nephropathy （DN）.MethodsActive ingredients with GLUT1 as a potential target， herbal medicines containing these ingredients and the targets of all these ingredients were screened by TCM Systems Pharmacology Database & Analysis Platform （TCMSP）. Target genes of DN were retrieved from the databases of GeneCards， OMIM， Drugbank and PharmGKB. The network of “herbs-compounds-targets” was constructed by Cytoscape software； PPI network was constructed through STRING database and Cytoscape software and topological parameters were performed for identifying core targets； molecular docking for GLUT1 acting upon active ingredients was performed for verifying binding capability. Analyses of Gene Ontology （GO） and Kyoto Encyclopedia of Gene and Genomes （KEGG） pathway enrichment were performed by Bioconductor R software.ResultsIsoliquiritigenin and emodin were two active TCM ingredients with GLUT1 as a potential target and there were a total of 53 acting targets. And 3371 DN-related and 40 intersection targets were identified and 16 were core targets. GLUT1 was one of core therapeutic targets for DN by isoliquiritigenin and emodin. Molecular docking results indicated that GLUT1 had stable binding to both of them. GO enrichment analysis showed that such biological processes as cellular response to abiotic stimulus and response to oxygen level were associated with the therapeutic effects of isoliquiritigenin and emodin on DN. KEGG enrichment analysis revealed that IL-17， TNF， AGE-RAGE and MAPK signaling pathway were associated with the therapeutic effects of isoliquiritigenin and emodin on DN.ConclusionIsoliquiritigenin and emodin are two active TCM ingredients with GLUT1 as a potential target. The therapeutic effects on DN are mediated through multiple targets and pathways. GLUT1 is one of core therapeutic targets of DN. Through direct and indirect actions， GLUT1 play important regulatory roles in the treatment of DN.